Potential Of Unconventional Low-Noise Propulsion Designs For Uav/Uam Applications - Sieradzki, A.; Kekus-Kumor, P.; Klimczyk, W. (My University, 2024)
The aim of this work is to evaluate the potential of unconventional low-noise propulsion designs for UAV and UAM vehicles. The paper presents three types of proposed solutions for reducing noise and improving propul- sion system performance. The first proposal addresses the issue of increased noise due to the interaction between propellers and supporting arms, exploring noise mitigation possibilities through a novel arm design. The subsequent two proposals involve coaxial co-rotating rotors and ducted rotors with compact duct design, which aim to improve aeroacoustic performance while maintaining the same propulsor diameter as the refer- ence isolated propeller. The paper presents the results of experimental tests of the prototype solutions con- ducted in an anechoic chamber in hover conditions. Comparisons with the reference case demonstrated sig- nificant potential of the proposed solutions, allowing to achieve noise reduction of up to 17.2 dB(A) and aero- dynamic efficiency improvement of up to 5%.